PENERAPAN ECOPRINT DI JORONG TALAWEH KECAMATAN LUAK KABUPATEN LIMAPULUH KOTA - Desra Imelda; Dini Yanuarm (LPPM Universitas Andalas, 2020)
Ecoprint as a craft to give fabric motifs with leaves is a very inspiring and environmentally friendly craft and is suitable for women to do because the manufacturing process is light and easy. The print results from ecoprint will never be the same because the process of transferring the leaf tannins onto the fabric occurs during steaming, this is one reason why ecoprint fabrics are quite expensive. The ecoprint training for members of the Silk Thread sewing group in Jorong Talaweh nagari Mungo, Luak sub-district, Fifty Cities district is aimed at preparing and providing skills so that they can make ecoprint an additional income generator for their family. This ecoprint training is carried out in two stages, first the training members are trained how to make an ecoprint, starting with processing the fabric so that the pores of the fabric are open and can receive leaf tannin transfers perfectly, then the fabric is ready to be printed. The ecoprinted fabrics are then used as functional items such as table mats, chair cushion covers, bags, and wallets by first being taught how to make patterns, cutting, sewing and finishing by giving sequins as a touch that adds aesthetic value.